Cross-linking treatment for better visual acuity - Senad Grišević; Fanka Gilevska; Alma Biščević; Melisa Ahmedbegović-Pjano; Ajla Pidro; Sudi Patel; Maja Bohač (Medicinski glasnik, 2019)
Aim: To correlate the maximum anterior sagittal curvature (Kmax) changes and uncorrected (UDVA) and corrected distance visual acuity (CDVA) in keratoconus patients after the cross-linking (CXL) procedure. Methods: Forty-four eyes of 34 patients with keratoconus were analysed after the standard Dresden protocol CXL procedure had been performed. All patients underwent complete preoperative examination with a follow-up of 12 months with focus on UDVA, CDVA and Oculus Pentacam (Scheimpflug technology) analysis. We analysed and correlated K max changes in the postoperative period of 12 months together with visual acuity changes. Results: Visual acuity improved significantly in the first 3 months after the procedure and even more significantly until the end of the first year. Even K max is the most relevant and most followed parameter for progression and regression of keratoconus, its lowering was not directly correlated with the visual acuity improvement (both uncorrected and corrected) in the first 6 months after corneal CXL procedure. K max was changed significantly in the period of 12 months post cross linking, but not in the first 6 months. Conclusion: Corneal CXL should be considered as a procedure not just for corneal stiffening and stabilization, but also for visual acuity improvement in keratoconus patients.
Keywords: corneal stroma; keratoconus; refractive errors; tomography